PENINGKATAN KUALITAS PRODUK MELALUI IbM KELOMPOK USAHA KECIL JAMU TRADISIONAL DI KECAMATAN SAMPANG - Siti Mujanah; Achmad Maqsudi; Rudi Santoso (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2015)
Herbal medicine from Madura Island, East Java Province has been known for a long time. Aside from being a medicine, herbs are also often drink as fresh healthy beverage, especially herbal carrying, but the problem of carrying medicinal is perishable product, which only survive within a day so that if it is not sale will be discarded. One of central medicinal to be developed